Inflation narratives - Peter Andre; Ingar Haaland; Christopher Roth; Johannes Wohlfart (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
We provide evidence on the stories that people tell to explain a historically notable rise in inflation using samples of experts, U.S. households, and managers. We document substantial heterogeneity in narratives about the drivers of higher inflation rates. Experts put more emphasis on demand-side factors, such as fiscal and monetary policy, and on supply chain disruptions. Other supply-side factors, such as labor shortages or increased energy costs, are equally prominent across samples. Households and managers are more likely to tell generic stories related to the pandemic or mismanagement by the government. We also find that households and managers expect the increase in inflation to be more persistent than experts. Moreover, narratives about the drivers of the inflation increase are strongly correlated with beliefs about its persistence. Our findings have implications for understanding macroeconomic expectation formation.
Keywords: D83; D84; E31; E52; E71; 330; Narratives; Inflation; Beliefs; Macroeconomics; Fiscal Policy; Monetary Policy